An empirical approach to modeling ion production rates in Titan's ionosphere II: Ion production rates on the nightside - Richard, M. S. (2015)
onization of neutrals by precipitating electrons and ions is the main source of Titan's nightside ionosphere. This paper has two goals: (1) characterization of the role of electron impact ionization on the nightside ionosphere for different magnetospheric conditions and (2) presentation of empirical ion production rates determined using densities measured by the Cassini Ion and Neutral Mass Spectrometer on the nightside. The ionosphere between 1000 and 1400 km is emphasized. We adopt electron fluxes measured by the Cassini Plasma Spectrometer-Electron Spectrometer and the Magnetospheric Imaging Instrument as classified by Rymer et al. (2009). The current paper follows an earlier paper (Paper I), in which we investigated sources of Titan's dayside ionosphere and demonstrated that the photoionization process is well understood. The current paper (Paper II) demonstrates that modeled and empirical ionization rates on the nightside are in agreement with an electron precipitation source above 1100 km. Ion production rate profiles appropriate for different Saturnian magnetospheric conditions, as outlined by Rymer et al., are constructed for various magnetic field topologies. Empirical production rate profiles are generated for deep nightside flybys of Titan. The results also suggest that at lower altitudes (below 1100 km) another source, such as ion precipitation, is probably needed.